Pregnancy after Aortic Root Replacement in Marfan's Syndrome: A Case Series and Review of the Literature - Dominique Williams; Kathryn J. Lindley; Melissa Russo; Jennifer Habashi; Harry C. Dietz; Alan C. Braverman (Thieme Medical Publishers, Inc., 2018)
Abstract Objectives We sought to characterize pregnancy-related aortic complications in women with Marfan's syndrome who had prior aortic root replacement. Study Design This is a retrospective case series study and literature review of women with Marfan's syndrome with pregnancy after aortic root replacement. We surveyed women with Marfan's syndrome who had successful pregnancy after aortic root replacement using the Marfan Foundation Website and from two large tertiary care Marfan's clinics. Clinical data, counseling information, and details of pregnancy-related aortic complications were compiled. A literature review was performed assessing aortic outcomes in women with Marfan's syndrome with pregnancy after aortic surgery. Results Fourteen women with 20 pregnancies were identified. Two women had three pregnancies following root replacement for aortic dissection. There were no aortic dissections during the 20 pregnancies. In contrast, aortic dissection was frequently reported in the literature. Conclusions Women with Marfan's syndrome who become pregnant following aortic root replacement remain at risk for distal aortic dissection related to pregnancy. The exact risk is difficult to quantify but is not zero and women should be counseled accordingly.